2020
DOI: 10.1021/acssuschemeng.0c04412
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bamboo-Mediated Biosynthesis of MnOx for Efficient Low-Temperature Propane Oxidation

Abstract: Small-size MnO x nanoparticles with good reducibility, fast lattice oxygen mobility, and large acid sites are first obtained by bamboo-mediated biosynthesis, showing promising propane (C 3 H 8 ) oxidation activity. The COO−, −C−O−, and −CO functional groups in bamboo powder (BP) act as complexing species, and the presence of organic carbon is responsible for bioreduction of Mn ions during calcination. The above bifunctional roles increase the content of Mn 2+ in MnO x , which contributes to large amounts of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…However, three signals at 284.1, 285.7, and 286.4 eV were identified from C 1 s spectrum is attributed to the presence of sp 2 carbon (C=C), sp 3 carbon (C-H, CÀC) and C-O functional group respectively (Figure 8d). [44][45][46][47][48][49][50] Hence, based on the obtained XPS spectra we confirmed the presence of phytochemicals and the respective valence states in δ-MnO 2 NPs.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Analysissupporting
confidence: 73%
“…However, three signals at 284.1, 285.7, and 286.4 eV were identified from C 1 s spectrum is attributed to the presence of sp 2 carbon (C=C), sp 3 carbon (C-H, CÀC) and C-O functional group respectively (Figure 8d). [44][45][46][47][48][49][50] Hence, based on the obtained XPS spectra we confirmed the presence of phytochemicals and the respective valence states in δ-MnO 2 NPs.…”
Section: X-ray Photoelectron Spectroscopy (Xps) Analysissupporting
confidence: 73%
“…After 13.8 wt % Na doping, the absorption bands at 1577, 1454, 1299, and 933 cm –1 were assigned to ν as (COO), ν s (COO), ν­(C–O), and δ­(O–H) vibrations of the carboxylate groups, respectively, and the double bands at 1181 and 1108 cm –1 were attributed to ν­(−C–O–CH 2 −) vibration of the fatty ether species. On the Pt 1 Co 1 /meso-Na x MnO y sample, the band at 1681 cm –1 was assigned to a carbonyl stretching vibration mode of acetone, and the one at 1486 cm –1 was due to the δ as (CH 3 ) vibration . The multiple signals at 1166 (or 1130), 1066, and 976 cm –1 were owing to ν­(C–C), ν­(C–O), and δ­(O–H) vibrations of the isopropoxide species, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…On the Pt 1 Co 1 /meso-Na x MnO y sample, the band at 1681 cm −1 was assigned to a carbonyl stretching vibration mode of acetone, 47 and the one at 1486 cm −1 was due to the δ as (CH 3 ) vibration. 50 The After the saturated adsorption of propane in a 2000 ppm propane + N 2 (balance) mixture flow (25 mL min −1 ) on MnO 2 at 250 °C, meso-Na x MnO y at 220 °C, or Pt 1 Co 1 /meso-Na x MnO y at 200 °C (all of them were denoted as adsaturation), 20 vol % O 2 was introduced for 30 min (all of them were denoted as O 2 -30 min), and in situ DRIFTS spectra of propane adsorption on the surface of MnO 2 , meso-Na x MnO y , and Pt 1 Co 1 /meso-Na x MnO y with the increase in temperature were recorded, as shown in Figure 10B,D,F, respectively. It can be found that some new absorption bands appear on the samples in the presence of O 2 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This observation confirms the oxidative consumption of MnO x to graphitized carbon, leading to the collapse of the layered structure of BAC. The weaker diffraction peaks around 36.6 • and 65.4 • were seemingly identified as (010) and (110) planes of the δ-MnO 2 structure (JCPDS 80-1098) and Mn 2 O 3 (JCPDS 00-031-0825), respectively[26,31]. In addition, a relatively sharp peak at approximately 26.6 • was evident in all samples because the oxidative consumption exposed inorganic SiO 2 to the sample surface[32].…”
mentioning
confidence: 92%
“…This uniquely aligned three-dimensional pore structure enhances the internal medium diffusion, and the micro-channels inside (i.e., cell lumens and pits on the cell walls) benefit the uniform and sufficient deposition of a catalyst on the surface of the support material, which improves the overall performance of adsorption and catalytic oxidation over the composites. Therefore, bamboo catalysts are usually regarded as a suitable support material expected to decompose gas pollutants, such as HCHO [25], C 3 H 8 [26], NO [27], and even for wastewater treatment [28].…”
Section: Introductionmentioning
confidence: 99%